2018
DOI: 10.22454/fammed.2018.688612
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Reception of a Required 4-Week Palliative Medicine Rotation

Abstract: Formal HPM training should be a required component in residency education and considerations should be given to the 4-week format. This rotation provides a model that can be implemented in other residency programs nationally. Implementation of this rotation may help close the enormous gap of patients not receiving quality EOL care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…A mandatory SPC rotation is not yet firmly anchored in the regulations of all specialty board certification; however, there is an increasing demand for this requirement-not only within an internal medicine residency-and a 6-month rotation in a palliative care unit as part of all specialized residencies should be discussed. 1,8,9,24 The analysis of our study clearly revealed a positive effect of a 6-to 12-month rotation. Physicians who rotated in SPC units showed a higher palliative knowledge compared to BCSs who had no SPC experience.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…A mandatory SPC rotation is not yet firmly anchored in the regulations of all specialty board certification; however, there is an increasing demand for this requirement-not only within an internal medicine residency-and a 6-month rotation in a palliative care unit as part of all specialized residencies should be discussed. 1,8,9,24 The analysis of our study clearly revealed a positive effect of a 6-to 12-month rotation. Physicians who rotated in SPC units showed a higher palliative knowledge compared to BCSs who had no SPC experience.…”
Section: Discussionsupporting
confidence: 53%
“…18,19 Furthermore, a 4-week rotation has a significant influence on the self-perception of physicians in their ability to provide end-of-life care . 9 In an effort to improve palliative care education, a mandatory rotation during oncological residency has recently been recommended. 20,21 However, physicians deemed a 1- to 4-week rotation as inadequate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a move may hold promise. One family medicine residency reported an increase in its residents’ comfort in end‐of‐life care after a required palliative care rotation was instituted …”
mentioning
confidence: 99%